2021
DOI: 10.3390/ijerph18126385
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Hand Hygiene Behaviour and Compliance of the General Public When Using Public Restrooms in Northern Ireland (NI) during the Initial Weeks of the Novel Coronavirus (COVID-19) Pandemic

Abstract: Background: The ongoing novel coronavirus (COVID-19) global pandemic has resulted in significant levels of morbidity and mortality worldwide, particularly among the elderly and immuno-suppressed groups. Although adequate hand hygiene (HH) behaviour and compliance is widely accepted as being the most effective self-protective measure in preventing the spread of diseases like COVID-19, previous research suggests that normal hand hygiene compliance is poor, but generally improves during a disease pandemic. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…(2) What are the demographic, housing, health, political, psychological and social factors associated with intentional non-adherence of SD rules by North London residents? London Jain et al [ 61 ] 17 July–10 Sept 2020 Between 1 st &2 nd wave Retrospective cohort To identify the proportion of symptomatic staff members attending workplaces after symptom onset or testing, and associated factors London Jorgensen et al [ 28 ] 19 March–16 May 2020 1st Repeated cross-sectional To investigate who is most likely to comply with advice from health authorities UK (4 nations) a Keyworth et al [ 62 ] 30th April 2020 1st Cross-sectional To evaluate challenges to adhering to government instructions UK Lawson et al [ 63 ] 10–20 March 2020 1st Direct observational To evaluate hand hygiene behaviour of the general public Northern Ireland MacIntyre et al [ 64 ] 10 July–27 July 2020 Cross-sectional To determine patterns of mask wearing and other infection prevention behaviours London a Maher et al [ 27 ] 9 March–6 April 2020 1st Network visualisation To map the emergence of opposing opinion-based groups and assess their implications for behaviour UK Margraf et al [ 65 ] May–June 2020 …”
Section: Resultsmentioning
confidence: 99%
“…(2) What are the demographic, housing, health, political, psychological and social factors associated with intentional non-adherence of SD rules by North London residents? London Jain et al [ 61 ] 17 July–10 Sept 2020 Between 1 st &2 nd wave Retrospective cohort To identify the proportion of symptomatic staff members attending workplaces after symptom onset or testing, and associated factors London Jorgensen et al [ 28 ] 19 March–16 May 2020 1st Repeated cross-sectional To investigate who is most likely to comply with advice from health authorities UK (4 nations) a Keyworth et al [ 62 ] 30th April 2020 1st Cross-sectional To evaluate challenges to adhering to government instructions UK Lawson et al [ 63 ] 10–20 March 2020 1st Direct observational To evaluate hand hygiene behaviour of the general public Northern Ireland MacIntyre et al [ 64 ] 10 July–27 July 2020 Cross-sectional To determine patterns of mask wearing and other infection prevention behaviours London a Maher et al [ 27 ] 9 March–6 April 2020 1st Network visualisation To map the emergence of opposing opinion-based groups and assess their implications for behaviour UK Margraf et al [ 65 ] May–June 2020 …”
Section: Resultsmentioning
confidence: 99%
“…In both samples, the hand washing scores were high [ 39 ]. Hand washing and the use of sanitizers have been reported to reduce the spread of SARS-CoV-2 since 2020 [ 43 , 44 , 45 ]. Experiences from the fight against COVID-19 can inspire future public health campaigns and show the public that high levels of hand hygiene can help solve the problem of the spread of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteriophage concentration used aimed to represent poorly washed/ unwashed/ contaminated hands, therefore a step of hand washing was not part of the study design and this may exaggerate the potential for airborne microbe transmission. Nonetheless, hands contaminated due to poor hand washing in public toilets remain common, with one study reporting over 83% of users not adequately washing their hands in the first weeks of COVID-19 pandemic ( 25 ), while other studies reported improvement of hand hygiene by healthcare professionals during the pandemic ( 26 , 27 ), but a decline in compliance over time ( 27 ). The infectious dose of inhaled virus remains unclear and so it cannot be assumed, of course, that facemask contamination is synonymous with infection.…”
Section: Discussionmentioning
confidence: 99%